2020
DOI: 10.1039/d0dt01497d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of site substitution of Pr doping in the lithium garnet system Li5La3Nb2O12

Abstract: We show that Pr is a rare example of an ambi-site dopant, being able to substitute onto either the La or Nb site in Li5La3Nb2O12, with the oxidation state determined by the site substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
2
6
1
Order By: Relevance
“…Ga-LLHO systems demonstrate high total ionic conductivity of 0.382 mS cm -1 at 28°C, and 1.04 mS cm -1 at 63°C, which represents an impressive value, especially since the pellet only achieved 87% relative density. The conductivity values are in line with many cubic LLZO (and other garnet) phases and are similar to Ga-LLZO values with higher relative densities 55,56,58,59,[62][63][64][65] . These values therefore represent notably higher conductivities for a doped LLHO garnet compared to the Al, Ta doped samples reported in the literature, while the fact that it has also been synthesised at considerably lower temperature is also significant 46,51,53 .…”
Section: Conductivity Measurementssupporting
confidence: 61%
“…Ga-LLHO systems demonstrate high total ionic conductivity of 0.382 mS cm -1 at 28°C, and 1.04 mS cm -1 at 63°C, which represents an impressive value, especially since the pellet only achieved 87% relative density. The conductivity values are in line with many cubic LLZO (and other garnet) phases and are similar to Ga-LLZO values with higher relative densities 55,56,58,59,[62][63][64][65] . These values therefore represent notably higher conductivities for a doped LLHO garnet compared to the Al, Ta doped samples reported in the literature, while the fact that it has also been synthesised at considerably lower temperature is also significant 46,51,53 .…”
Section: Conductivity Measurementssupporting
confidence: 61%
“…The high-density of Ga-NLZO pellets (93%) is notable as it is accomplished relatively simply, and are higher than our previous reports for La based garnets prepared under similar conditions, where densities ≤ 90% are more commonly observed 32,53,54,86 .…”
Section: See Tablecontrasting
confidence: 56%
“…Overall the evaluation of Nd based garnets has revealed that, despite many having rather low room temperature conductivity, the conductivity of Ga-NLZO is similar to other lithium garnets prepared under similar conditions, despite the smaller lattice parameters 34,42,50,52,55,[82][83][84][85] . The high conductivity observed for Ga-NLZO is likely due, in part, to the good sinterability of this composition leading to higher density (93% theoretical).…”
Section: See Tablementioning
confidence: 89%
“…[12][13][14] The highly conductive cubic phase can be stabilised through the creation of lithium vacancies, and the optimum conductivity is found for lithium contents of 6.4-6.6 per garnet formula unit. [15][16][17][18][19][20][21][22][23][24][25] In addition, to facilitate the practical application of ASSBs, issues such as high interfacial resistances between the electrode and electrolyte, and the lithium dendrite penetration problem within solid state electrolytes have attracted much attention in recent years. [26][27][28][29] The interfacial impedance between the garnet and electrode mainly arises from the poor contact in association with microscopic voids and grain boundaries of garnet, as well as an insulating Li 2 CO 3 surface layer formed in air initiated by the proton/lithium exchange at the surface.…”
Section: Introductionmentioning
confidence: 99%